Design, Synthesis and Biological Evaluation of Benzothiazole-thiophene Hybrids: A New Class of Potent Antimicrobial Agents - Saraswat, Pankaj; Jeyabalan, Govindasamy; Hassan, Mohd Z.; Ahsan, Mohammad J. (Anti-Infective Agents, 2018)
Introduction: In the last two-three decades, antimicrobial infections have developed extreme multiple drug-resistance and the appearance of these resistant strains is one of the biggest threats to global health. The benzothiazole moiety is of interest to many researchers on the grounds that they constitute a vital class of heterocyclic compounds exhibiting enormous chemotherapeutic activities. In the drug design aspect, structure activity relationship (SAR) study is an area of exploring and continuously refining the structural or physical properties for evoking the promising biological effects. Methods: The present study discusses the synthesis of new antimicrobial candidates using the pharmacophore hybrids of benzothiazole and thiophene scaffold. In an attempt to identify potential lead antimicrobial agents, a number of N-(substituted-benzothiazol-2-yl)thiophene-2-carboxamidederivatives were efficiently synthesized by conventional synthesis and screened in order to evaluate for their antibacterial activity against Staphylococcus aureus (ATCC-25923) and Escherichia coli (ATCC-25922) and antifungal activity against Aspergillus niger (ATCC- 9029) and Candida albicans (ATCC-90028) in DMF by serial plate dilution method. Results: Amongst the synthesized compounds, compound 3g showed significant antibacterial activity and antifungal activity. Rest of the compounds showed moderate to less antibacterial activity against both S. aureus and E. Coli. and antifungal activity against A. niger and C. albicans. The SAR studies demonstrate that introducing an electron-withdrawing group at the aromatic ring has favorable effect on the antimicrobial activity. A correlation study was also used to establish the relationship between the activity and physicochemical parameter clogP. Titled compounds could be a promising template for future antimicrobial drug development. Discussion: The synthesized compounds were characterized by elemental and spectral data analysis. Antimicrobial activity of the title compounds has been evaluated by varying the substituents in the benzothiazol moiety.
Keywords: antimicrobial